Cellular and Humoral Immune Response to a Third Dose of BNT162b2 COVID-19 Vaccine – A Prospective Observational Study - Herzberg, Jonas; Fischer, Bastian; Becher, Heiko; Becker, Ann-Kristin; Honarpisheh, Human; Guraya, Salman Yousuf; Strate, Tim; Knabbe, Cornelius (Frontiers in Immunology, 2022)
Background Since the introduction of various vaccines against SARS-CoV-2 at the end of 2020, infection rates have continued to climb worldwide. This led to the establishment of a third dose vaccination in several countries, known as a booster. To date, there has been little real-world data about the immunological effect of this strategy. Methods We compared the humoral- and cellular immune response before and after the third dose of BioNTech/Pfizer vaccine BNT162b2, following different prime-boost regimen in a prospective observational study. Humoral immunity was assessed by determining anti-SARS-CoV-2 binding antibodies using a standardized quantitative assay. In addition, neutralizing antibodies were measured using a commercial surrogate ELISA-assay. Interferon-gamma release was measured after stimulating blood-cells with SARS-CoV-2 specific peptides using a commercial assay to evaluate the cellular immune response. Results We included 243 health-care workers who provided blood samples and questionnaires pre- and post- third vaccination. The median antibody level increased significantly after the third vaccination dose to 2663.1 BAU/ml vs. 101.4 BAU/ml (p < 0.001) before administration of the booster dose. This was also detected for neutralizing antibodies with a binding inhibition of 99.68%  0.36% vs. 69.06% +- 19.88% after the second dose (p < 0.001). 96.3% of the participants showed a detectable T-cell-response after the booster dose with a mean interferon-gamma level of 2207.07 mIU/ml +- 1905 mIU/ml. Conclusion This study detected a BMI-dependent antibody increase after the third dose of BNT162b2 following different vaccination protocols. All participants showed a significant increase in their immune response. This, in combination with the low rate of post-vaccination-symptoms underlines the potential beneficial effect of a BNT162b2-booster dose.